2009
DOI: 10.2353/ajpath.2009.080330
|View full text |Cite
|
Sign up to set email alerts
|

DEK Proto-Oncogene Expression Interferes with the Normal Epithelial Differentiation Program

Abstract: Overexpression of the DEK gene is associated with multiple human cancers, but its specific roles as a putative oncogene are not well defined. DEK transcription was previously shown to be induced by the high-risk human papillomavirus (HPV) E7 oncogene via E2F and Rb pathways. Transient DEK overexpression was able to inhibit both senescence and apoptosis in cultured cells. In at least the latter case, this mechanism involved the destabilization of p53 and the decreased expression of p53 target genes. We show her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 57 publications
3
76
0
Order By: Relevance
“…Thus, DEK may maintain the tumor-initiating activity of solid tumors, at least partly through modulation of these transcriptional regulators, suggesting that a common molecular pathway functions in the maintenance of both liquid and solid CSCs. It has been shown that DEK overexpression interferes with differentiation and expands the population of undifferentiated keratinocytes (Wise-Draper et al, 2009b), supporting the contention that DEK also has a significant role in normal epithelial stem cell maintenance.…”
Section: Molecular Classification Of Pulmonary Endocrine Tumorsmentioning
confidence: 50%
“…Thus, DEK may maintain the tumor-initiating activity of solid tumors, at least partly through modulation of these transcriptional regulators, suggesting that a common molecular pathway functions in the maintenance of both liquid and solid CSCs. It has been shown that DEK overexpression interferes with differentiation and expands the population of undifferentiated keratinocytes (Wise-Draper et al, 2009b), supporting the contention that DEK also has a significant role in normal epithelial stem cell maintenance.…”
Section: Molecular Classification Of Pulmonary Endocrine Tumorsmentioning
confidence: 50%
“…To explore this, we used immunofluorescence to determine DEK localization throughout mitosis in NIKS cells, a near-diploid spontaneously immortalized keratinocyte cell line that harbors low DEK expression levels. 30 While DEK is known to bind chromatin constitutively during interphase, we noted its marked absence from DNA during certain phases of mitosis ( Fig. 1B and 1C).…”
Section: Resultsmentioning
confidence: 98%
“…30 Primary antibodies used for DEK were as follows: DEK (1:1000; http://www.bdbiosciences.com/us/reagents/research/antibodiesbuffers/cell-biology-reagents/cell-biology-antibodies/purifiedmouse-anti-human-dek-2dek/p/610948), DEK-Aviva (1:1000; http://www.avivasysbio.com/dek-antibody-n-terminal-regionp100637-t100.html), DEK antibody K-877 (1:10,000, a polyclonal antibody; gift from Ferdinand Kappes), a DEK cocktail including the 3 described antibodies and DEK polyclonal rabbit from Proteintech (1:1000; http://www.ptglab.com/Products/ DEK-Antibody-16448-1-AP.htm). Other antibodies include a tubulin (1:5000; http://www.sigmaaldrich.com/catalog/product/ sigma/t9026), pH3-S10 (1:1000; http://www.cellsignal.com/ product/productDetail.jsp?productIdD9701), H3 (1:1000; http://www.cellsignal.com/products/primary-antibodies/9715), pan-actin (1:20,000; a gift from James Lessard, Cincinnati Children's Hospital Medical Center, Cincinnati, OH, USA).…”
Section: Western Blot Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiation results in DEK downregulation in human promyelocytic HL-60 cells and in human foreskin keratinocytes, and in turn, overexpression of DEK counteracts cell differentiation (Savli et al, 2002;Wise-Draper et al, 2009b) and promotes proliferation and transformation of epithelial cells (Wise-Draper et al, 2009a). The DEK gene was originally described during early embryonic development, but is preferentially expressed in actively proliferating cells and can inhibit cell differentiation, senescence, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%